2019
DOI: 10.29060/taps.2019-4-1/oa2025
|View full text |Cite
|
Sign up to set email alerts
|

Depression and stressful life events among medical students during undergraduate career: Findings from a medical school in South Asia

Abstract: Medical students face significant psychological stress and adverse life events throughout their student career. The aim of this study was to assess the prevalence of depression among medical undergraduates in a medical faculty in Sri Lanka. Methods: A cross-sectional study using a self-administrated, validated questionnaire was conducted among 300 undergraduate medical students of the University of Colombo, Sri Lanka. Prevalence of depression was assessed using Beck Depression Inventory (BDI). The data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…While a study in Nigeria recorded the prevalence of depression among university students was 58.2% measured by the Patient Health Questionnaire-9 (PHQ-9) [27]. Another survey among medical undergraduates in the Faculty of Medicine in Sri Lanka using the Beck Depression Inventory (BDI) revealed that the prevalence of depression 19% [28]. Possible explanations for the variation in the prevalence of depression found in this present study and previous studies conducted among university students are likely due to the change in the instruments used.…”
Section: Discussionmentioning
confidence: 99%
“…While a study in Nigeria recorded the prevalence of depression among university students was 58.2% measured by the Patient Health Questionnaire-9 (PHQ-9) [27]. Another survey among medical undergraduates in the Faculty of Medicine in Sri Lanka using the Beck Depression Inventory (BDI) revealed that the prevalence of depression 19% [28]. Possible explanations for the variation in the prevalence of depression found in this present study and previous studies conducted among university students are likely due to the change in the instruments used.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because medical students are likely to experience long study hours, stress related to clinical practices,[ 56 ] and pressure from repeated academic evaluations. [ 57 ]…”
Section: Discussionmentioning
confidence: 99%
“…25 Previous research has linked mental health in university students with factors like gender, age, academic year, university type, and sources of personal expenses. [26][27][28] Studies in Bangladesh, Egypt, and Sri Lanka showed that female students are more prone to depression, [26][27][28] whereas older students experience more mental health symptoms. 29 It also rises with the academic year.…”
Section: Introductionmentioning
confidence: 99%